2022
DOI: 10.3390/ph15030375
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole Treatment for Invasive Fungal Infections in Pediatric Patients

Abstract: This work’s objective was to evaluate the safety of isavuconazole (ISA) as a treatment or prophylaxis for invasive fungal infections (IFIs) in immunocompromised children. IFI was reported as proven or probable according to international definitions. Therapeutic drug monitoring was performed using mass tandem spectrometry to quantify trough plasma concentrations. Targeted ISA levels were 2–4 mg/L, as reported in adult series. Nine patients received ISA as a curative treatment, and six received ISA as prophylaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Clinical breakpoints could favour a greater inclusion of isavuconazole in clinical practice, considering that active trials demonstrated its non-inferiority relative to echinocandins for the primary treatment of fungemia and invasive fungal infections [31]. Clinical trials have also been established to test isavuconazole safety against invasive fungal infections among paediatric patients [32]. Moreover, isavuconazole has been compared to voriconazole in invasive aspergillosis, showing high effectiveness [33].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical breakpoints could favour a greater inclusion of isavuconazole in clinical practice, considering that active trials demonstrated its non-inferiority relative to echinocandins for the primary treatment of fungemia and invasive fungal infections [31]. Clinical trials have also been established to test isavuconazole safety against invasive fungal infections among paediatric patients [32]. Moreover, isavuconazole has been compared to voriconazole in invasive aspergillosis, showing high effectiveness [33].…”
Section: Discussionmentioning
confidence: 99%
“…A total of six patients experienced adverse effects during treatment (elevation of transaminases, bilirubin or creatinine), but all were able to complete the treatment [ 110 ]. Zimmerman et al had recently similar results in a cohort of 15 hemato-oncological patients (10 of these later also underwent HSCT) treated with isavuconazole: 9 received the drug as curative treatment, 6 as prophylaxis; no patient showed progressive fungal disease and 6 had complete response at day 90 [ 111 ]. No suspension of chemotherapy or immunosuppression was needed and no drug-to-drug interaction was noted.…”
Section: Novel Drugs For Contrasting Invasive Fungal Diseasesmentioning
confidence: 97%
“…Most of the current studies showed that a daily therapeutic dose of 100 mg was a safe and effective regimen for children with IM weighing less than 30 kg. The first ISA blood concentration monitoring can be performed on the 10th day of ISA treatment and every 2 weeks thereafter (Zimmermann et al, 2022). Similarly, Arrieta et al (2021) evaluated the effects of ISA on the pharmacokinetics, safety and tolerability of 46 immunocompromised children, and the results showed that ISA was well tolerated at 10 mg/kg intravenously or orally, children could achieve plasma concentrations similar to adults.…”
Section: Immentioning
confidence: 99%
“…Most of the current studies showed that a daily therapeutic dose of 100 mg was a safe and effective regimen for children with IM weighing less than 30 kg. The first ISA blood concentration monitoring can be performed on the 10th day of ISA treatment and every 2 weeks thereafter ( Zimmermann et al., 2022 ). Similarly, Arrieta et al.…”
Section: Clinical Efficacymentioning
confidence: 99%